KOMUNIKASI PERSUASIF KH MOHAMAD ASO SAMSUDDIN MELALUI KAJIAN KITAB ‘NASHOIHUL IBAD’ PADA SANTRI ASRAMA NURUL QONI’ PUTRA. - Gus Vikri; Mohamat Hadori; Aminul ‘Alimin (Fakultas Dakwah Universitas Ibrahimy, 2023)
Communication is a basic human activity as a creature that plays an individual and social role. In the daily activities of humans, if they cannot communicate with each other with various interactions in the real world and the virtual world, then it can be said that they will be far behind, confused and lost. In carrying out daily life activities, learning in communication theories has various benefits that can change the person invited to communicate to change according to the wishes of the communicator without any coercion. In that case the communication activity is called persuasive communication. Persuasive communication is a process of communication between the communicator and the communicant whose aim is to influence the communicant to change according to what the communicator wants without coercion. In this paper, the author focuses on the formulation of the problem which discusses the forms of persuasive communication carried out by KH Mohamad Aso Samsuddin with his students at the Nurul Qoni’ Putra Dormitory, which is one of the branch dormitories in the Salafiyah Syafi’iyah Islamic Boarding School Sukorejo Situbondo. By using qualitative research methods, researchers combine the results of data collection techniques through observation, interviews, and documentation. Producing 9 forms of persuasive communication carried out by KH Mohamad Aso Samsuddin with his students at the Nurul Qoni’ Putra Dormitory, by accessing the recitation of the Nashoihul Ibad book. Among others; Inviting students to increase learning motivation. Invite students to study solely because of Allah. Invite students to apply knowledge. Invite students to improve morals. Invite students to love. Submission of material strengthening of the Nashoihul Ibad book with references to other books. Clarifying the delivery of material from the Nashoihul Ibad book with the story of salafunas sholeh. Clarify the delivery of material from the Nashoihul Ibad book by linking the duties and responsibilities of the board as umana’ pesantren. Blend into the language of the students and also the daily activities of the students. With the existence of 4 communication techniques namely Association, Integration, Rewards and Order.